EGS P05 Surgical Same Day Emergency Care at a District General Hospital - Our Experience. (7th December 2022) - Sultan, Ahmed; Hussain, Mohammad Iqbal; Sellahewa, Chaminda; Bird, Jonathan; Glover, Gemma
Abstract: Background: Surgical Same day emergency care (SDEC) is a new service started at a medium sized district general hospital (DGH) since November 2021. The surgical SDEC service is divided into Theatre (ambulatory theatres) and non-theatre (Hot Clinic) pathways aiming at improving patient experience, and reducing length of stay (LOS), by introducing a pathway through which patients are assessed, diagnosed, and initiated treatment and discharge on the same day for common emergency surgical conditions of gallstone disease, appendectomy, painful hernia, and abscesses. The service delivery planned with the existing facilities leading to structured fewer admissions, increased diagnostics, coordinating the patient flow with preop assessments, day case theatre utilisation and post-operative criteria led discharge. The Surgical SDEC is now established, and we continue to audit to benchmark success, recommend improvement and for quality assurance. Methods: It's a prospective data collection of patients admitted under general surgery with the above common surgical emergency presentations over 6 months period since the start of the service in November 2021. The inclusion criteria were stable patients of ASA grade 1 and 2, BMI less than 40 kg/m2, and with social support. The unstable patients, ASA 3 or more and without social support were excluded. The postoperative follow up was arranged with virtual ward, clinics and in the event a post-surgery hot clinic review. Results: From 15th November 2021 to 27th May 2022, 192 surgical operations were carried out. 130 Laparoscopic cholecystectomies, 22 hernia repairs, 13 diagnostic laparoscopies, and 27 abscesses incision and drainage. There were 77 male patients and 115 female patients with age ranging from 20 to 88 years old. About 70% of the patients were successfully discharged on the same day with a readmission rate of 3.6%. The cholecystectomy patients had a mean waiting time of 3.2 days and almost all cases were done within a week of admission. All the other cases including appendectomy were performed either the same day or the following day. Conclusions: Surgical Same Day Emergency Care service proved to be a step forward for improving patient care. It allows the same day diagnostics and treatment, and reduces the length of stay, prevents readmissions, improves the quality of care, and helps recovery following the impacts of the pandemic. Finally, it has a significant financial benefit by decreasing readmissions, and it also utilisation of hospital beds more desired cases.